Redating Nepotian’s Usurpation and the Coinage of Magnentius - Caza, Shawn (KOINON: The International Journal of Classical Numismatic Studies, 2018)
A re-examination of the historical sources, based on an idea put forward in April 2010 by Curtis Clay, supports the possibility that the date of the brief rebellion of Nepotian at Rome should be changed from the traditionally accepted June 350 to May-June 351. Such a change appears to provide for a closer match with many historical sources, better fits the sequence of other historical events, and better explains the distribution and layout of the coinage of Magnentius. Such a change necessitates a redating of most of the phases of Magnentius’ coinage, from those outlined by Pierre Bastien in his magnus opus Le monayage de Magnence, and a revision of several other numismatic assumptions. This article lays out the justification for changing the date of Nepotian’s rebellion and provides a revised dating for Magnentius’ bronze coinage.